Assessment of mucosal changes associated with nasal splint in a rabbit model - ŞAHİN, NURHAN; TAN, MEHMET; KALCIOĞLU, MAHMUT TAYYAR; Sahin, NURHAN; BAYINDIR, TUBA; ŞAMDANCI, EMİNE; Filiz, Aliye (My University, 2015)
Introduction: There is no consensus on duration of the nasal splint after nasal septum surgeries. The pressure of nasal splint on the mucosa may cause tissue necrosis and nasal septum perforation.